Mode of onset of dropped head syndrome and efficacy of conservative treatment. (7th July 2020) - Kusakabe, Takuya; Endo, Kenji; Sawaji, Yasunobu; Suzuki, Hidekazu; Nishimura, Hirosuke; Matsuoka, Yuji; Murata, Kazuma; Takamatsu, Taichiro; Maekawa, Asato; Aihara, Takato; Yamamoto, Kengo
Purpose: The initial treatment of dropped head syndrome (DHS) is basically nonsurgical, but the mode of onset of DHS and efficacy of conservative treatment have not been fully clarified. Methods: The subjects were 38 DHS patients without neuromuscular disease (11 men and 27 women, average age 74.5 years). Cervical collar, physical therapy, and temporary medication for cervical pain were provided for all DHS patients. The following parameters were measured on lateral global spine standing radiographs: sagittal vertical axis (SVA), cervical sagittal vertical axis, C2–C7 angle, first thoracic slope, thoracic kyphosis, lumbar lordosis, sacral slope, pelvic tilt, and pelvic incidence. According to the mode of onset of DHS, the subjects were classified into acute-onset group (<3 months) and chronic-onset group (≥3 months). Results: Acute- and chronic-onset DHS were observed in 20 and 18 patients, respectively. A history of cervical trauma was involved in nine and two cases of acute- and chronic-onset DHS, respectively. Acute-onset DHS included more balanced-SVA (B-SVA: −30 mm <SVA ≤40 mm) than chronic-onset DHS. In conservative cases, the recovery rate was better in acute-onset DHS with B-SVA. In acute-onset DHS treated conservatively, the recovery rate was significantly poor in cervical trauma cases. Conclusions: Acute-onset DHS includes more balanced SVA and a history of cervical trauma, while acute-onset DHS without a history of cervical trauma has better prognosis by conservative treatment. Surgical indications for DHS should be carefully determined, and sufficient conservative treatment is essential.